Program Bank Sampah Binor Lestari Sebagai Lingkungan Berkelanjutan Di Desa Binor, Kecamatan Paiton, Kabupaten Probolinggo - Edhi Siswanto; Nadiya Amalia Putri (Empat Sembilan Publisher, 2026)
This study examines the role of the Binor Lestari Waste Bank as an innovative community-based model for sustainable environmental management in Binor Village, Paiton District, Probolinggo Regency, Indonesia. The research addresses increasing household waste generation, limited waste-sorting practices, and the need to transition from conventional collect-and-dispose systems toward reduction- and recycling-oriented management. Methods: A descriptive qualitative research design was employed. Data was collected through field observations, in-depth interviews with waste bank managers and community members, documentation review, and questionnaire distribution. Data was analyzed through systematic classification, interpretation, and triangulation to ensure validity and contextual accuracy. Results: The findings indicate that the Binor Lestari Waste Bank significantly contributes to improving environmental awareness, encouraging household-level waste segregation, and fostering active community participation. In 2024, approximately 313 kg of recyclable waste was managed, generating IDR 313,600 in economic value. From January to September 2025, 202 kg of waste was collected, producing IDR 426,750. Beyond measurable economic returns, the program strengthens social cohesion, supports local environmental education, and integrates with village-level sustainability initiatives. However, challenges remain in participation consistency, operational resources, and systematic waste collection scheduling. The Binor Lestari Waste Bank demonstrates that community-driven waste management can simultaneously achieve ecological, social, and economic benefits. As a village-based environmental governance model, it supports sustainable development through participatory mechanisms and local institutional collaboration. Strengthening administrative systems, expanding community engagement, and improving logistical support will enhance long-term sustainability and replicability in other rural contexts.